Glycerol amendment enhances biosulfidogenesis in acid mine drainage-affected areas: An incubation column experiment - Ilin, A. M.; van der Graaf, C. M.; Yusta, I.; Sorrentino, A.; Sánchez-Andrea, I.; Sánchez-España, J. (Frontiers in Bioengineering and Biotechnology, 2022)
Microbial sulfate (SO42-) reduction in Acid Mine Drainage (AMD) environments can ameliorate the acidity and extreme metal concentrations by consumption of protons via the reduction of SO42- to hydrogen sulfide (H2S) and the concomitant precipitation of metals as metal sulfides. The activity of sulfate-reducing bacteria can be stimulated by the amendment of suitable organic carbon sources in these generally oligotrophic environments. Here, we used incubation columns (IC) as model systems to investigate the effect of glycerol amendment on the microbial community composition and its effect on the geochemistry of sediment and waters in AMD environments. The ICs were built with natural water and sediments from four distinct AMD-affected sites with different nutrient regimes: the oligotrophic Filón Centro and Guadiana acidic pit lakes, the Tintillo river (Huelva, Spain) and the eutrophic Brunita pit lake (Murcia, Spain). Physicochemical parameters were monitored during 18 months, and the microbial community composition was determined at the end of incubation through 16S rRNA gene amplicon sequencing. SEM-EDX analysis of sediments and suspended particulate matter was performed to investigate the microbially-induced mineral (neo)formation. Glycerol amendment strongly triggered biosulfidogenesis in all ICs, with pH increase and metal sulfide formation, but the effect was much more pronounced in the ICs from oligotrophic systems. Analysis of the microbial community composition at the end of the incubations showed that the SRB Desulfosporosinus was among the dominant taxa observed in all sulfidogenic columns, whereas the SRB Desulfurispora, Desulfovibrio and Acididesulfobacillus appeared to be more site-specific. Formation of Fe3+ and Al3+ (oxy)hydroxysulfates was observed during the initial phase of incubation together with increasing pH while formation of metal sulfides (predominantly, Zn, Fe and Cu sulfides) was observed after 1-5 months of incubation. Chemical analysis of the aqueous phase at the end of incubation showed almost complete removal of dissolved metals (Cu, Zn, Cd) in the amended ICs, while Fe and SO42- increased towards the water-sediment interface, likely as a result of the reductive dissolution of Fe(III) minerals enhanced by Fe-reducing bacteria. The combined geochemical and microbiological analyses further establish the link between biosulfidogenesis and natural attenuation through metal sulfide formation and proton consumption.